Contrasting long-term temperature trends reveal minor changes in projected potential evapotranspiration in the US Midwest - Bruno Basso (Nature Portfolio, 2021)
Warming in the US Midwest is believed to increase the water needed to grow crops. This study finds that, on the contrary, due to rising rainfall and minimum temperature, and decreasing maximum temperature, potential crop water demand remains unchanged despite the warming climate.